Dive into Close Reading : Strategies for Your K-2 Classroom. - Lapp, Diane (Professional Resources Ser., 2017)
Give grades K-2 students the tools they need to be successful using this must-have guide. It includes sample lessons showing the key elements of a close reading lesson as well as strategies for analyzing and selecting a text and how to support students.